Express each of the following in standard form

y= 1/4x - 1/3

-4(-1/4x + y +1/3)=(0)-4

-3(1x - 4y -4/3)=(0)-3

-3x+12y+4=0

-3x+12y=-4

The answer is 3x-12y=4

I don't know what I did wrong, please help.(Itwasntme)

Printable View

- April 27th 2010, 03:07 PMbuckIntercepts & standard form
Express each of the following in standard form

y= 1/4x - 1/3

-4(-1/4x + y +1/3)=(0)-4

-3(1x - 4y -4/3)=(0)-3

-3x+12y+4=0

-3x+12y=-4

The answer is 3x-12y=4

I don't know what I did wrong, please help.(Itwasntme) - April 27th 2010, 03:17 PMharish21